The Perancangan Sistem Penyiram Tanaman Otomatis Berbasis IoT di Sekolah Alam Purwakarta - Faradilla Amanda Zalfa; Ahmad Anas; Rahmat Supriyatna (Pusat Riset dan Inovasi Nasional, 2026)
The application of the Internet of Things (IoT) in agriculture (Smart Farming) has proven to be crucial for increasing productivity, efficiency, and crop quality. This study focuses on the design and development of an IoT-based automatic plant irrigation system as a solution to overcome the challenges of imprecise manual irrigation at Sekolah Alam Purwakarta. This system aims to optimize water allocation and make it easier for workers to control plant care in real-time through an IoT-based application. The method used is Research and Development (R&D) with the ADDIE model approach. The results show that the de-veloped system is capable of automatically activating irrigation based on soil moisture readings (with a threshold of 50% RH), while displaying real-time data for control. This allows workers to know the exact water requirements and effectively prevent drought or overwatering conditions. Overall, the design of this system provides an effective solution for water conservation and work efficiency in supporting plant care at Sekolah Alam Purwakarta.